Research handbook on the protection of intellectual property under WTO rules - Correa, Carlos María.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2010)
This comprehensive Handbook provides an in-depth analysis of the origin and main substantive provisions of the TRIPS Agreement, the most influential international treaty on intellectual property currently in force.
pt. I. History, interpretation and principles -- pt. II. Substantive rights.
Includes bibliographical references and index.
Keywords: Intellectual property (International law); Electronic books